2012
DOI: 10.1007/s10571-012-9852-0
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Protects Against Hypoxia Mimetic-Induced Autophagy by Targeting the HIF-1α Pathway in Retinal Ganglion Cells

Abstract: Hypoxia-induced retinal ganglion cell (RGC) death has been proposed to be the critical event in the pathophysiology of glaucoma. Therefore, delaying or halting RGC degeneration, known as neuroprotection, is a novel and promising approach with potential clinical applications for treating glaucoma. In this study, we investigate hypoxia-induced cell death of RGCs and the underlying mechanisms of N-acetylcysteine (NAC) as a neuroprotectant. To establish a model for chemical hypoxia-induced cell death, RGC-5 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Moreover, several in vitro studies also demonstrated that suppression of both apoptosis and autophagy enhanced cell survival [22,41]. Apart from apoptosis, CoCl 2 -induced hypoxia also triggered autophagy in rat cardiomyoblasts (H9c2) and retinal ganglion cells (RGC-5) cell line [22,42]. A study reported that the anti-apoptotic protein Bcl-2 acts as a pro-survival protein and negatively regulates autophagy, indicating the crosstalk between apoptosis and autophagy [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several in vitro studies also demonstrated that suppression of both apoptosis and autophagy enhanced cell survival [22,41]. Apart from apoptosis, CoCl 2 -induced hypoxia also triggered autophagy in rat cardiomyoblasts (H9c2) and retinal ganglion cells (RGC-5) cell line [22,42]. A study reported that the anti-apoptotic protein Bcl-2 acts as a pro-survival protein and negatively regulates autophagy, indicating the crosstalk between apoptosis and autophagy [43].…”
Section: Discussionmentioning
confidence: 99%
“…6). Similarly, Yang et al (2012) reported that NAC increased the amounts of phosphorylated mTOR and Akt proteins in RGC-5 cells but these authors did not measure protein synthesis. The underlying mechanism whereby NAC affects the expression of these proteins is still unknown.…”
Section: Figmentioning
confidence: 98%
“…Conversely, BSO or diethylmaleate reduced cell proliferation and GSH concentration without affecting protein synthesis, while promoting protein physiological fluid and is readily transported by cells (Lai et al 2012;Lee et al 2013). Therefore, NAC provides a direct and convenient means to increase the intracellular concentration of glutathione (GSH, the reduced form of glutathione) in many tissues and cell types (Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…N-acetylcysteine-mediated neuroprotection is also mediated by targeting the hypoxia-inducible factor-1a pathway and counteracting the autophagic cell death [80]. It has low toxicity and it is able to cross the placenta and blood--brain barrier [81].…”
Section: Resultsmentioning
confidence: 99%